Generalized Extension of Referred Trigeminal Pain due to Greater Occipital Nerve Entrapment - Jung-woo Hyung; Byung-chul Son (Case Reports in Neurological Medicine)
We report a very rare case of referred pain caused by greater occipital nerve (GON) entrapment, inducing spontaneous pain in the whole body as well as in the trigeminal nerve region of the face and head. It has already been reported that entrapment of the GON can induce referred pain in the ipsilateral limb as well as the ipsilateral hemiface. A 42-year-old female patient presented with chronic pain in her gums, jaw angle, submandibular region, retro-auricular suboccipital, and temporo-occipital vertex that had been ongoing for four years. As the patient’s head pain and facial pain became severe, severe spontaneous pain occurred in the arm, waist, and both lower extremities. This patient’s pain in the occipital and neck, spontaneous pain in the face, jaw, and whole body improved with decompression of the GON. Anatomical basis of pain referral to the facial trigeminal area caused by chronic GON entrapment is convergence of nociceptive inflow from high cervical C1–C3 structures and trigeminal orofacial area in the dorsal horn of the cervical spinal cord from the C2 segment up to the medullary dorsal horn (MDH). The major afferent contribution among the suboccipital and high cervical structure is mediated by spinal root C2 that is peripherally represented by the GON. Chronic noxious input from GON entrapment can cause sensitization and hypersensitivity in second order neurons in the trigeminocervical complex (TCC) and MDH in the caudal trigeminal nucleus and high cervical cord. Generalized extension of referred pain due to GON entrapment is thought to involve two possible pathophysiologies. One is the possibility that generalized pain is caused by sensitization of third-order nociceptive neurons in the thalamus. Another speculation is that spontaneous pain may occur throughout the body due to dysfunction of the descending brain stem pain-modulating pathway by sensitization and hyperexcitation of the MDH and trigeminal brainstem sensory nuclear complex (TBSNC).